Pengembangan Media Pembelajaran Berbasis Ispring Suite 8 Pada Materi Perwasitan Matakuliah Teori dan Praktek Bola Voli 1 Tahun Akademik 2018/2019 - Antonius Prasetyo Hadi (IKIP Budi Utomo Malang, 2019)
: The use of learning media is one of the critical success factors in higher education, therefore an educator must have innovation to use of learning media. The purpose of this research is to develop learning media based on the Inspiring Suit 8 on arbitration material courses of theoretical and practice for Volleyball 1 academic year 2018/2019 at IKIP Budi Utomo Malang. The existence of media will be a big successful support in learning process, so that students do not feel boredom because of the weaknesses of the lecturers, in which they are unable to provided good learning variation or even have difficulty in conveying or transferring knowledge. The research was descriptive qualitative design. The research subjects were students of Physical Education, Health, and Recreation Study Program who took volleyball theory and practice courses in the even semester academic year 2018/2019. The instruments used were the media expert review questionnaire, the learning expert questionnaire, and the trial analysis questionnaire. The questionnaire will be analyzed to see the feasibility of the developed media. Based on the data results review by media expert volleyball, media learning expert and field trials, it can be concluded that media developed is useful in learning process. In addition, it is used to provide independent motivation, which can be used in lesson for students.